Pengaruh Jus Tomat terhadap Penurunan Tekanan Darah pada Lansia dengan Hipertensi - Yudi Muammar; Parmo Sinaga (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This literature review explores the effects of tomato juice on lowering systolic and diastolic blood pressure in elderly individuals with hypertension. Hypertension is a prevalent condition among the elderly and a major risk factor for cardiovascular diseases. The objective of this review is to evaluate the effectiveness of tomato juice as a non-pharmacological intervention to manage hypertension. The research methodology involved a comprehensive review of studies published between 2020 and 2024, sourced from reputable databases such as Google Scholar and ScienceDirect. The findings indicate that tomato juice, rich in potassium and lycopene, significantly reduces blood pressure in elderly patients. Potassium helps regulate sodium levels in the body, while lycopene provides antioxidant benefits and promotes vascular health. Although tomato juice demonstrates potential as an effective and natural remedy for hypertension, further research with larger sample sizes and longer durations is needed to confirm its long-term benefits. The implications of these findings suggest that tomato juice could be considered as a supportive therapy for hypertension management in the elderly, though it should not replace conventional antihypertensive medications.